2009
DOI: 10.1364/ao.48.001520
|View full text |Cite
|
Sign up to set email alerts
|

Spectral multiplexing method for digital snapshot spectral imaging

Abstract: We propose a spectral imaging method for piecewise "macropixel" objects, which allows a regular digital camera to be converted into a digital snapshot spectral imager by equipping the camera with only a disperser and a demultiplexing algorithm. The method exploits a "multiplexed spectrum" intensity pattern, i.e., the superposition of spectra from adjacent different image points, formed on the image sensor of the digital camera. The spatial image resolution is restricted to a macropixel level in order to acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Results coming from these studies have shown some advantages, but also several problems related to the use of CS in this field, such as the availability of large-size, high speed modulators. Some developments have led to patent registration, like the Tel-Aviv Digital Snapshot Spectral Imager 13 . Research in developing hyperspectral imaging system with CS technology is driven by the opportunity of reducing the data throughput of sensors, which can be challenging especially for satellite missions.…”
Section: State Of the Art Of Cs Instrumentsmentioning
confidence: 99%
“…Results coming from these studies have shown some advantages, but also several problems related to the use of CS in this field, such as the availability of large-size, high speed modulators. Some developments have led to patent registration, like the Tel-Aviv Digital Snapshot Spectral Imager 13 . Research in developing hyperspectral imaging system with CS technology is driven by the opportunity of reducing the data throughput of sensors, which can be challenging especially for satellite missions.…”
Section: State Of the Art Of Cs Instrumentsmentioning
confidence: 99%
“…Spectral imaging can also use a diffraction element such as a grating or prism, where the spectrum is scanned pixel-by-pixel or line-by-line [9]. Each method has its pros and cons that depend on the measurement parameters and the actual application such as acquisition time, spectral and/or spatial resolution [10][11][12]. A few different commercial spectral cameras are available that are based on these methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a mathematic problem, deconvolution is well developed and several great solutions are proposed to deal with this problem, such as Richardson-Lucy deconvolution [10] , which is employed to reconstruct spectrum in Ref. [11]. In Fig.…”
mentioning
confidence: 99%